Coaching Culture Implementation Strategy in Improving Company Performance: PT Neural Technologies Indonesia Case Study - Setiatmoko, Trie; Ma’arif, Mohamad Syamsul; Suhendi, Suhendi (Pelopor Publikasi Akademika, 2025)
In today’s competitive business environment, companies face the dual challenges of improving performance and retaining qualified employees. One strategy gaining recognition is the development of a coaching culture, which has been shown to positively impact both organizational performance and employee retention. This study examines the implementation of a coaching culture at PT Neural Technologies Indonesia, analyzing the strategies employed and their effects on company performance. Using a mixed-method approach, this study combines quantitative data from SEM-PLS with qualitative insights from in-depth interviews and strategy analysis through the Eckenrode method. The results indicate that a strong coaching culture, driven by leadership commitment, coaching competence, and integration into management processes, significantly enhances company performance and employee retention. Notably, the ESQ 3.0 Coaching model was effective in fostering intrinsic motivation and aligning individual goals with organizational objectives. Practical recommendations for enhancing coaching culture include prioritizing leadership commitment, offering continuous coaching competency development, and embedding coaching practices into the organizational structure. These strategies are crucial for sustaining a coaching culture that contributes to long-term performance improvement and employee engagement. This study highlights the importance of leadership in creating a supportive coaching environment and suggests that a well-implemented coaching culture is integral to achieving business success.